Four new species of the Stegana ornatipes species group (Diptera: Drosophilidae) from Yunnan, China, with DNA barcoding information - Zhang, Yuan; Chen, Hong-Wei (Zootaxa, 2015)
Fore new species of Stegana (Steganina) ornatipes species group are found from Yunnan, China: S. (S.) angustifoliacea sp. nov., S. (S.) crinata sp. nov., S. (S.) nigripes sp. nov. and S. (S.) polysphyra sp. nov. The DNA sequences of the mitochondrial COI gene with BOLD Process ID and GenBank accession numbers are provided for the Chinese species.